2019
DOI: 10.7454/jessd.v2i2.1035
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Habitat, Distribution, and Diversity of Anopheles SPP in Kemelak Bindung Langit Village, Ogan Komering Ulu Regency, South Sumatra

Abstract: Malaria is an infectious disease caused by Plasmodium and is transmitted through the bite of a female Anopheles vector. Ogan Komering Ulu (OKU) is a district in South Sumatra that is endemic to malaria. The study aims to determine habitat type, environmental factors that influence larvae development, and distribution of Anopheles larvae. The experiment was conducted from January to February 2019 in the Kelurahan Kemelak Bindung Langit, OKU. Species identification was carried out in the Entomology Laboratory, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…The species of An. kochi was found within a pH range of 5.35 -6, consistent with the finding of Maretasari et al (2019) that identified the same species of larvae at pH 5. Additionally, Sugiarti et al (2020) reported finding these larvae within a pH range of 5 -6.6.…”
Section: Discussionsupporting
confidence: 90%
“…The species of An. kochi was found within a pH range of 5.35 -6, consistent with the finding of Maretasari et al (2019) that identified the same species of larvae at pH 5. Additionally, Sugiarti et al (2020) reported finding these larvae within a pH range of 5 -6.6.…”
Section: Discussionsupporting
confidence: 90%
“…vagus found was 6.40-8.10 (mean 7.37). In Ogan Komering Ulu Regency, Maretasari et al (2019) reported the pH value in the rice fields of An. vagus habitat was in acidic pH (5-6).…”
Section: Resultsmentioning
confidence: 99%
“…Several habitats such as rice fields (20), ponds (21), puddles of flooded soil, grassy fields with shrubs and shade plants that hold water, and even dug wells are breeding places for A. vagus (22). The ditch around the settlement ( 21) collects rainwater and household waste overgrown with tall grass is also favored by this species (23), especially those with a mud bottom (24) (25). Even in Simpang Empat village, Lengkiti, Ogan Komering Ulu, South Sumatra, this species is commonly found in puddles on roads (26), including the ground holes made by heavy vehicles which are filled with water (21,26).…”
Section: Discussionmentioning
confidence: 99%
“…Poorly maintained vacant land, which can hold freshwater with little acidity or neutral water, is also highly preferred by A. vagus (25,27). Apart from marshy areas in the lowlands (24), A. vagus can also be found in the highlands (28).…”
Section: Discussionmentioning
confidence: 99%